Carbon black as well as preparation method and application thereof

By mixing cellulose biomass materials with acid solution and calcining, carbon black with excellent physical and chemical adsorption ability, conductivity and hydrophilicity was prepared, which solved the problems of cumbersome preparation process of the existing carbon black and limited impact on battery performance, achieving improvement of battery performance.

CN119551658APending Publication Date: 2025-03-04DONGGUAN DONGYANG SOLAR SCI RES & DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411882700.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The preparation process of existing conductive carbon black is cumbersome, energy consumption is high, and has limited impact on the charging and discharging process of the battery.

Method used

Carbon black with excellent physical and chemical adsorption ability, conductivity and hydrophilicity were prepared by mixing cellulose biomass materials with acid solution, calcining and decomposing treatment.

Benefits of technology

This method simplifies the preparation process of carbon black, reduces costs, improves the overall performance of carbon black, improves the solvent resistance and peel strength of the battery, and reduces the adverse impact of the shedding of the active layer on the battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005198579480000091
    Figure BDA0005198579480000091
  • Figure BDA0005198579480000101
    Figure BDA0005198579480000101
  • Figure BDA0005198579480000121
    Figure BDA0005198579480000121
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to carbon black and a preparation method and application thereof. The preparation method comprises the following steps: (1) mixing a cellulose biomass material with an acid solution, and then carrying out solid-liquid separation to obtain a solid; and (2) mixing the solid obtained in the step (1), an alkali metal ion-containing compound and a nitrogen-containing organic matter and / or a phosphorus-containing organic matter, calcining and removing impurities to obtain the carbon black. The carbon black disclosed by the invention is wide in raw material source, simple in preparation process and relatively low in cost; the formed carbon black has excellent physical and chemical adsorption capacity, conductivity and hydrophilicity, is excellent in comprehensive performance, and can effectively improve the performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to carbon black and a preparation method and application thereof. Background Art

[0002] With the continuous development of the battery industry, carbon-coated current collectors have been widely promoted and applied for their advantages of improving the positive electrode peeling strength and battery performance. Conductive carbon black, one of the main solid phase components of the current carbon-coated slurry, is mainly prepared by cracking hydrocarbon raw materials under high temperature reaction. The preparation process is very cumbersome and energy-intensive, and the cost of the hydrocarbon raw materials used is generally high; more importantly, the conductive carbon black cracked at high temperature only has a physical anchoring force on the main components of the positive electrode active material, and has little effect on the deintercalation process of active ions during the battery's charge and discharge process.

[0003] Therefore, in order to solve the above problems, it is necessary to develop a conductive carbon black with a wide source of raw materials, relatively simple synthesis, and certain chemical adsorption force, in order to achieve some performance improvements of lithium batteries. Summary of the invention

[0004] In view of the above problems, the present application provides a carbon black and a preparation method and application thereof. The raw materials for the preparation of the carbon black are widely available, the preparation process is simple, and the cost is low. The formed carbon black has excellent physical and chemical adsorption capacity, conductivity and hydrophilicity, and has excellent comprehensive performance, which can effectively improve the performance of the battery.

[0005] In a first aspect, the present application provides a method for preparing carbon black, the preparation method comprising the following steps:

[0006] (1) mixing a cellulosic biomass material and an acid solution to form a suspension, and then performing solid-liquid separation to obtain a solid;

[0007] (2) The solid obtained in step (1), the alkali metal ion-containing compound, and the nitrogen-containing organic matter and / or the phosphorus-containing organic matter are mixed, calcined and impurity-removed to obtain carbon black.

[0008] In the technical solution of the embodiment of the present application, the above process is simple and low-cost. When the formed carbon black is used for the pole piece, such as forming a composite current collector, the performance of the pole piece can be improved, thereby improving the overall performance of the battery; specifically:

[0009] In step (1), cellulose biomass material is used as the main synthetic raw material, which has a wide source and low cost; the cellulose biomass material and the acid solution are mixed. The main process is to firstly leach out the impurities in the cellulose biomass material with the acid solution, and also to activate the hydroxyl groups on the surface of the cellulose biomass material, thereby improving its hydrophilicity and facilitating the subsequent solid-liquid separation.

[0010] In step (2), during the calcination process, the alkali metal ion compound can catalyze the thermal reaction process of the cellulose biomass material, change the original pore structure of the cellulose biomass material itself, and help adjust the specific surface area of ​​the carbon black within an appropriate range, so that the physical adsorption capacity and conductivity of the carbon black are improved. The combination of nitrogen-containing organic matter and / or phosphorus-containing organic matter further improves the chemical adsorption capacity and conductivity of the carbon black. Therefore, the preparation method can improve the physical and chemical adsorption capacity and conductivity of the carbon black. Furthermore, when the carbon black obtained by the above method is used in the composite current collector, it can improve the solvent resistance of the composite current collector in the electrode, improve the peeling strength between the composite current collector and the active layer, and reduce the adverse effect of the active layer shedding on the battery performance; and the carbon black obtained by the above method is conducive to reducing the internal resistance of the electrode, further improving the performance of the battery.

[0011] In addition, alkali metal ion compounds can catalyze the thermal reaction process of cellulose biomass materials, produce abundant oxygen-containing groups on the surface of cellulose biomass materials, improve the chemical activity of the material surface, adjust the oil absorption value of carbon black within an appropriate range, and improve the hydrophilicity of carbon black, so that carbon black can be better dispersed in water during application. While reducing the processing difficulty, it is conducive to the formation of stable performance electrodes, thereby improving the performance of the battery.

[0012] In summary, the carbon black formed by the preparation method of the present application has excellent physical and chemical adsorption capacity, conductivity and hydrophilicity. When used in batteries, such as forming a composite current collector, it can improve the solvent resistance of the composite current collector in the pole piece, improve the peeling strength between the composite current collector and the active layer, and reduce the adverse effect of the active layer shedding on the battery performance; and the carbon black obtained by the above method is conducive to reducing the internal resistance of the pole piece and improving the performance of the battery; in addition, the carbon black obtained by the above method is conducive to forming a pole piece with stable performance while reducing the difficulty of processing, further improving the performance of the battery.

[0013] In the technical solution of the implementation mode of the present application, nitrogen-containing organic matter is used as an example to illustrate that nitrogen-containing organic matter is easy to decompose and produce nitrogen-rich gas during the calcination process. Therefore, carbon black can be nitrogen-doped during the formation process; for example, the cleavage of the "nitrogen-nitrogen" bond of nitrogen during high temperature can achieve nitrogen doping of cellulose biomass materials, achieving the purpose of nitrogen enrichment treatment, and the formed carbon black is beneficial to improve the cycle and rate performance of the battery. The reason why nitrogen-doped carbon black can improve the performance of the battery is that the electronegativity of carbon is 2.5, while the electronegativity of nitrogen is 3.1. The comparison of electronegativity shows that nitrogen is more likely to attract electrons during the formation of the compound, so that the formation of "lithium-nitrogen" bonds during the electrochemical reaction is easy to "lithium-carbon" bonds, achieving strong chemical adsorption of lithium and improving various performances of the battery; phosphorus-containing organic matter has a similar process, which will not be repeated here.

[0014] As an example, the cellulose biomass material described in the present application may be crushed and sieved (for example, a 200-mesh screen may be used) before being mixed with the acid solution to facilitate subsequent operations.

[0015] Preferably, in step (1), the cellulosic biomass material comprises any one of bamboo straws, hemp straws or corn straws, or a combination of at least two of them.

[0016] Preferably, in step (1), the acid used in the acid solution includes any one of nitric acid, hydrochloric acid or sulfuric acid, or a combination of at least two of them.

[0017] In the present application, there is no limitation on the concentration of the acid solution. As an example, the molar concentration of the acid solution may be 1-5 mol / L, such as 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, etc.

[0018] Preferably, in step (1), the mixed raw materials also include a dispersant.

[0019] In the present application, there is no restriction on the amount of dispersant added in the system, as long as the dispersion requirements of the cellulose biomass material are met. As an example, based on the total volume of the acid solution and the dispersant, the concentration of the dispersant is 1-10g / L, such as 1g / L, 2g / L, 3g / L, 4g / L, 5g / L, 6g / L, 7g / L, 8g / L, 9g / L, 10g / L, etc. As an example, the mass ratio of the dispersant to the cellulose biomass material is (0.01-0.06): 1, wherein 0.01-0.06 can be 0.02, 0.03, 0.04, 0.05, etc.

[0020] In the technical solution of the implementation mode of the present application, a dispersant is used in combination with an acid solution to treat the cellulosic biomass material, which is beneficial for the cellulosic biomass material to form a stable suspension, can effectively disperse the solid phase material in the suspension, and can also effectively wash away the impurity components in the cellulosic biomass material and increase the surface hydroxyl groups, thereby facilitating subsequent further processing.

[0021] Preferably, the dispersant comprises any one of polyvinyl pyrrolidone (PVP), poloxamer or polyethylene glycol, or a combination of at least two thereof.

[0022] In the present application, in step (1), there is no limitation on the mixing method, as long as the cellulosic biomass material can be evenly dispersed in the acid solution.

[0023] As an example, the mixing method includes stirring.

[0024] Preferably, the mixing is carried out in a water bath, wherein the temperature of the water bath may be 30-70°C, such as 30°C, 40°C, 50°C, 60°C, 70°C, etc.; and / or;

[0025] The mixing time is 2-5 hours, for example 2 hours, 3 hours, 4 hours, 5 hours, etc., and more preferably 3 hours.

[0026] In the present application, the solid-liquid separation also includes washing and drying the solid matter.

[0027] Preferably, in step (2), the alkali metal ion-containing compound includes any one of potassium citrate, potassium oxalate, potassium acetate, potassium glycerol, potassium sulfate, potassium nitrate, potassium hydroxide or potassium chloride, or a combination of at least two thereof.

[0028] Preferably, in step (2), based on the total mass of the solid matter after drying as 100%, the mass of the alkali metal ion compound is greater than 0% and less than or equal to 300%, for example, 5%, 10%, 50%, 100%, 150%, 200%, 250%, 300%, etc.

[0029] Preferably, in step (2), the nitrogen-containing organic matter includes any one of urea, melamine or biuret, or a combination of at least two thereof.

[0030] Preferably, the phosphorus-containing organic matter includes any one of triphenylphosphine, triphenylphosphine oxide or tri(o-tolyl)phosphine, or a combination of at least two thereof.

[0031] Preferably, in step (2), based on the total mass of the dried solid matter as 100%, the mass of the nitrogen-containing organic matter and / or phosphorus-containing organic matter is greater than 0% and less than or equal to 300%, for example, 5%, 10%, 50%, 100%, 150%, 200%, 250%, 300%, etc.

[0032] Preferably, in step (2), the calcination temperature is 700-900°C, more preferably 750-900°C, further preferably 750-850°C, further preferably 800°C, for example 700°C, 750°C, 800°C, 850°C, 900°C, etc.; and / or;

[0033] The calcination time is 1-3 h, more preferably 2 h, for example 1 h, 1.5 h, 2 h, 2.5 h, 3 h, etc.

[0034] In the present application, there is no limitation on the temperature rise program of roasting. As an example, the temperature rise rate of roasting can be 1-10°C / min, such as 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, etc.

[0035] Preferably, in step (2), the impurity removal method includes mixing the calcined material with an aliphatic organic acid to remove alkali metal ions.

[0036] In the technical solution of the implementation mode of the present application, the aliphatic organic acid has no special biological activity and does not contain other non-metallic elements that may have an impact other than hydrogen, carbon, and oxygen, and can achieve efficient impurity removal of potassium ions.

[0037] In the present application, there is no restriction on the amount of aliphatic organic acid added. As an example, its concentration can be 0.1-3 mol / L, such as 0.1 mol / L, 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, etc.

[0038] In the present application, there is no limit on the mixing time during impurity removal, and it is designed according to the quality of the calcined material to fully remove the alkali metal ions. As an example, the mixing time can be 0.1-5h, such as 0.1h, 1h, 2h, 3h, 4h, 5h, etc.

[0039] Preferably, the aliphatic organic acid comprises oxalic acid.

[0040] In the technical solution of the implementation mode of the present application, oxalic acid is a general aliphatic organic acid, has no special biological activity, and does not contain other non-metallic elements that may have an impact except hydrogen, carbon, and oxygen. At the same time, oxalic acid itself has a strong acidity and has a better leaching effect on alkali metal ions. Therefore, the use of oxalic acid can achieve efficient removal of alkali metal ions.

[0041] In the present application, the impurity removal may also include washing, drying or grinding operations, such as rinsing with water, drying, and grinding for later use.

[0042] As a preferred technical solution, the preparation method comprises the following steps:

[0043] (1) mixing a cellulosic biomass material, an acid solution and a dispersant to form a suspension, and then performing solid-liquid separation to obtain a solid;

[0044] (2) The solid obtained in step (1), the alkali metal ion-containing compound, and the nitrogen-containing organic matter and / or the phosphorus-containing organic matter are mixed, and calcined at 700-900° C. for 1-3 h, and the calcined material is mixed with an aliphatic organic acid to remove the alkali metal ions to obtain carbon black.

[0045] In a second aspect, the present application provides a carbon black, which is obtained by the preparation method described in the first aspect.

[0046] Preferably, the specific surface area of ​​the carbon black is 80-130 m 2 As an example, the specific surface area of ​​the carbon black is 80 m 2 / g, 85m 2 / g, 90m 2 / g, 95m 2 / g、100m 2 / g、105m 2 / g, 110m 2 / g, 120m 2 / g, 125m 2 / g, 130m 2 / g, etc.

[0047] Preferably, the oil absorption value of the carbon black is 200-285mL / 100g. As an example, the oil absorption value of the carbon black is 200mL / 100g, 220mL / 100g, 230mL / 100g, 240mL / 100g, 250mL / 100g, 260mL / 100g, 270mL / 100g, 280mL / 100g, etc. However, the larger the oil absorption value, the better. When the oil absorption value is too large, the dispersion effect of carbon black in the aqueous solution during the preparation of the carbon coating slurry is poor, which affects the preparation of the slurry.

[0048] In a third aspect, the present application provides a composite current collector, the composite current collector comprising a current collector and a carbon layer disposed on at least one surface of the current collector;

[0049] The carbon layer includes the carbon black obtained by the preparation method described in the first aspect, or the carbon black described in the second aspect.

[0050] In the present application, the composite current collector can be used for a positive electrode sheet or a negative electrode sheet, that is, the current collector can be a positive electrode current collector (such as aluminum foil, etc.) or a negative electrode current collector (such as copper foil, etc.).

[0051] In a fourth aspect, the present application provides an electrode plate, which includes the carbon black obtained by the preparation method described in the first aspect, or the carbon black described in the second aspect, or the composite current collector described in the third aspect.

[0052] In the present application, the electrode plate can be a positive electrode plate or a negative electrode plate.

[0053] In a fifth aspect, the present application provides a battery, comprising the carbon black obtained by the preparation method described in the first aspect, or the carbon black described in the second aspect, or the composite current collector described in the third aspect, or the electrode plate described in the fourth aspect.

[0054] Compared with the prior art, the technical solution of the present application has at least the following beneficial effects:

[0055] (1) The raw materials used in the preparation method of the present application are widely available, the process is simple and the cost is low.

[0056] (2) The carbon black formed by the preparation method of the present application has excellent physical and chemical adsorption capacity, conductivity and hydrophilicity, and has excellent comprehensive performance, which can effectively improve the performance of the battery.

[0057] (3) The carbon black formed by the preparation method of the present application, when used in a battery, such as forming a composite current collector, can improve the solvent resistance of the composite current collector in the electrode, improve the peel strength between the composite current collector and the active layer, and reduce the adverse effects of the active layer shedding on the battery performance; and the carbon black obtained by the above method is beneficial to reducing the internal resistance of the electrode, thereby improving the performance of the battery; in addition, the carbon black obtained by the above method is beneficial to forming a electrode with stable performance while reducing the processing difficulty, thereby further improving the performance of the battery.

[0058] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. DETAILED DESCRIPTION

[0059] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0060] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the description and claims of this application and any variations thereof are intended to cover non-exclusive inclusions.

[0061] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0062] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "2-10" means that all real numbers between "2-10" are listed in this document, and "2-10" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is an integer 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0063] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists, A and B exist at the same time, and B exists. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0064] Example 1

[0065] This embodiment provides a method for preparing carbon black, and the preparation method comprises the following steps:

[0066] (1) 50 g of crude bamboo straw powder was added to 300 mL of 3 mol / L nitric acid solution (added with 5 g / L PVPK30), heated at 50 °C and stirred continuously for 3 h. After solid-liquid separation, the mixture was washed with pure water and dried to obtain a solid.

[0067] (2) The solid obtained in step (1) was ground and mixed evenly with potassium citrate and urea in a mass ratio of 1:1:1, and then transferred to a porcelain boat and calcined at 700° C. for 2 h in a tubular furnace in a nitrogen atmosphere (the heating rate during the calcination process was controlled at 5° C. / min).

[0068] (3) The calcined sample was immersed in 300 mL of 1 mol / L oxalic acid solution and stirred continuously at room temperature for 1 h. After solid-liquid separation, the calcined sample powder was washed with pure water, and then dried and ground to obtain a black solid powder, i.e., the carbon black.

[0069] Example 2

[0070] This embodiment provides a method for preparing carbon black, and the preparation method comprises the following steps:

[0071] (1) 50 g of crude bamboo straw powder was added to 300 mL of 3 mol / L nitric acid solution (added with 5 g / L PVPK30), heated at 50 °C and stirred continuously for 3 h. After solid-liquid separation, the mixture was washed with pure water and dried to obtain a solid.

[0072] (2) The solid obtained in step (1) was ground and mixed evenly with potassium citrate and urea in a mass ratio of 1:1:1, and then transferred to a porcelain boat and calcined at 800° C. for 2 h in a tubular furnace in a nitrogen atmosphere (the heating rate during the calcination process was controlled at 5° C. / min).

[0073] (3) The calcined sample was immersed in 300 mL of 1 mol / L oxalic acid solution and stirred continuously at room temperature for 1 h. After solid-liquid separation, the calcined sample powder was washed with pure water, and then dried and ground to obtain a black solid powder, i.e., the carbon black.

[0074] Example 3

[0075] This embodiment provides a method for preparing carbon black, and the preparation method comprises the following steps:

[0076] (1) 50 g of crude bamboo straw powder was added to 300 mL of 3 mol / L nitric acid solution (added with 5 g / L PVPK30), heated at 50 °C and stirred continuously for 3 h. After solid-liquid separation, the mixture was washed with pure water and dried to obtain a solid.

[0077] (2) The solid obtained in step (1) was ground and mixed evenly with potassium citrate and urea in a mass ratio of 1:1:1, and then transferred to a porcelain boat and calcined at 900° C. for 2 h in a tubular furnace in a nitrogen atmosphere (the heating rate during the calcination process was controlled at 5° C. / min).

[0078] (3) The calcined sample was immersed in 300 mL of 1 mol / L oxalic acid solution and stirred continuously at room temperature for 1 h. After solid-liquid separation, the calcined sample powder was washed with pure water, and then dried and ground to obtain a black solid powder, i.e., the carbon black.

[0079] Example 4

[0080] This embodiment provides a method for preparing carbon black, and the preparation method comprises the following steps:

[0081] (1) 50 g of crude bamboo straw powder was added to 300 mL of 3 mol / L nitric acid solution (added with 5 g / L PVPK30), heated at 50 °C and stirred continuously for 3 h. After solid-liquid separation, the mixture was washed with pure water and dried to obtain a solid.

[0082] (2) The solid obtained in step (1) was ground and mixed evenly with potassium citrate and urea in a mass ratio of 1:1:1, and then transferred to a porcelain boat and calcined at 800° C. for 1 h in a tubular furnace in a nitrogen atmosphere (the heating rate during the calcination process was controlled at 5° C. / min).

[0083] (3) The calcined sample was immersed in 300 mL of 1 mol / L oxalic acid solution and stirred continuously at room temperature for 1 h. After solid-liquid separation, the calcined sample powder was washed with pure water, and then dried and ground to obtain a black solid powder, i.e., the carbon black.

[0084] Example 5

[0085] This embodiment provides a method for preparing carbon black, and the preparation method comprises the following steps:

[0086] (1) 50 g of crude bamboo straw powder was added to 300 mL of 3 mol / L nitric acid solution (added with 5 g / L PVPK30), heated at 50 °C and stirred continuously for 3 h. After solid-liquid separation, the mixture was washed with pure water and dried to obtain a solid.

[0087] (2) The solid obtained in step (1) was ground and mixed evenly with potassium citrate and urea in a mass ratio of 1:1:1, and then transferred to a porcelain boat and calcined at 800° C. for 3 h in a tubular furnace in a nitrogen atmosphere (the heating rate during the calcination process was controlled at 5° C. / min).

[0088] (3) The calcined sample was immersed in 300 mL of 1 mol / L oxalic acid solution and stirred continuously at room temperature for 1 h. After solid-liquid separation, the calcined sample powder was washed with pure water, and then dried and ground to obtain a black solid powder, i.e., the carbon black.

[0089] Example 6

[0090] This embodiment provides a method for preparing carbon black, and the preparation method comprises the following steps:

[0091] (1) Add 50 g of crude bamboo straw powder to 300 mL of 3 mol / L hydrochloric acid solution (added with 5 g / L PVPK30), heat at 40°C and stir continuously for 5 h. After solid-liquid separation, wash with pure water and dry to obtain a solid.

[0092] (2) The solid obtained in step (1) is ground and mixed evenly with potassium oxalate and melamine in a mass ratio of 1:1:3, and then transferred to a porcelain boat and calcined at 800° C. for 2 h in a tubular furnace in a nitrogen atmosphere (the heating rate during the calcination process is controlled at 5° C. / min).

[0093] (3) The calcined sample was immersed in 300 mL of 1 mol / L oxalic acid solution and stirred continuously at room temperature for 1 h. After solid-liquid separation, the calcined sample powder was washed with pure water, and then dried and ground to obtain a black solid powder, i.e., the carbon black.

[0094] Example 7

[0095] This embodiment provides a method for preparing carbon black, and the preparation method comprises the following steps:

[0096] (1) 50 g of crude bamboo straw powder was added to 300 mL of 3 mol / L sulfuric acid solution (added with 5 g / L PVPK30), heated at 70°C and stirred continuously for 1 h. After solid-liquid separation, the mixture was washed with pure water and dried to obtain a solid.

[0097] (2) The solid obtained in step (1) was ground and mixed evenly with potassium chloride and biuret in a mass ratio of 1:3:1, and then transferred to a porcelain boat and calcined at 800°C for 2h in a tubular furnace in a nitrogen atmosphere (the heating rate during the calcination process was controlled at 5°C / min).

[0098] (3) The calcined sample was immersed in 300 mL of 1 mol / L oxalic acid solution and stirred continuously at room temperature for 1 h. After solid-liquid separation, the calcined sample powder was washed with pure water, and then dried and ground to obtain a black solid powder, i.e., the carbon black.

[0099] Example 8

[0100] The difference between this embodiment and embodiment 2 is that the dispersant PVP is not included, and the rest is the same as embodiment 2.

[0101] Examples 9-10

[0102] The difference between Examples 9-10 and Example 2 is that the mass ratios of the solid obtained in step (1) to potassium citrate and urea are 1:3.5:1 (Example 9) and 1:1:3.5 (Example 10), respectively, and the rest are the same as Example 2.

[0103] Comparative Example 1

[0104] This comparative example provides a method for preparing carbon black, which comprises the following steps:

[0105] (1) 50 g of crude bamboo straw powder was added to 300 mL of 3 mol / L nitric acid solution (added with 5 g / L PVPK30), heated at 50 °C and stirred continuously for 3 h. After solid-liquid separation, the mixture was washed with pure water and dried to obtain a solid.

[0106] (2) The solid obtained in step (1) was ground and mixed evenly with potassium citrate in a mass ratio of 1:1, and then transferred to a porcelain boat and calcined at 800° C. for 2 h in a tubular furnace in a nitrogen atmosphere (the heating rate during the calcination process was controlled at 5° C. / min).

[0107] (3) The calcined sample was immersed in 300 mL of 1 mol / L oxalic acid solution and stirred continuously at room temperature for 1 h. After solid-liquid separation, the calcined sample powder was washed with pure water, and then dried and ground to obtain a black solid powder, i.e., the carbon black.

[0108] Comparative Example 2

[0109] This comparative example provides a method for preparing carbon black, which comprises the following steps:

[0110] (1) 50 g of crude bamboo straw powder was added to 300 mL of 3 mol / L nitric acid solution (added with 5 g / L PVPK30), heated at 50 °C and stirred continuously for 3 h. After solid-liquid separation, the mixture was washed with pure water and dried to obtain a solid.

[0111] (2) The solid obtained in step (1) and urea are ground and mixed uniformly in a mass ratio of 1:1, and then transferred to a porcelain boat and calcined at 800° C. for 2 h in a tubular furnace in a nitrogen atmosphere (the heating rate during the calcination process is controlled at 5° C. / min).

[0112] (3) The calcined sample was immersed in 300 mL of 1 mol / L oxalic acid solution and stirred continuously at room temperature for 1 h. After solid-liquid separation, the calcined sample powder was washed with pure water, and then dried and ground to obtain a black solid powder, i.e., the carbon black.

[0113] Comparative Example 3

[0114] This comparative example provides a commercial conductive carbon black purchased from Swiss company Termeco with the brand name Super P Li.

[0115] Performance Testing

[0116] 1. Performance test of carbon black

[0117] (1) Specific surface area: According to the national standard GB / T 3780.5-2017 Carbon black Part 5: Determination of specific surface area by CTAB method, the test data results are obtained by testing using the CTAB method.

[0118] (2) Oil absorption value: According to the national standard GB / T 3780.4-2017 Carbon black Part 2: Determination of oil absorption value, the oil absorption value tester is used to perform the test by the instrumental method to obtain the test data results.

[0119] The test results are summarized in Table 1.

[0120] Table 1

[0121]

[0122]

[0123] From the analysis of Comparative Example 1, Comparative Example 2 and Example 2, it can be seen that the specific surface area and oil absorption value of the carbon black prepared by adding alkali metal ion compounds, nitrogen-containing organic matter and / or phosphorus-containing organic matter in step (2) of the present application are in an appropriate range, and the carbon black performance is better.

[0124] From the analysis of Comparative Example 3 and Example 2, it can be seen that the carbon black obtained by the preparation method described in the present application has a more appropriate specific surface area and oil absorption value and better performance than the products of the prior art.

[0125] 2. Performance test of carbon coated aluminum foil

[0126] (1) Preparation of carbon-coated aluminum foil: 16 parts by weight of an aqueous polyacrylic acid binder (solid content of 25%), 15 parts by weight of isopropanol, 3.4 parts by weight of carbon black of each embodiment and comparative example, 0.6 parts by weight of KS-6 graphite, 0.35 parts by weight of Tween 40 and 0.5 parts by weight of sodium carboxymethyl cellulose were dispersed in 64.15 parts by weight of pure water at a speed of 500 rpm, and then sand-milled at a speed of 700 rpm for 3 h, and then the slurry was taken out and degassed by low-speed stirring for 1 h;

[0127] Then, the surface of the battery aluminum foil was single-sided coated with a 3 μm wire rod on an automatic coating machine at a coating rate of 100 mm / s, and transferred to a 100° C. oven for drying for 3 min to obtain a single-sided carbon-coated aluminum foil.

[0128] (2) Solvent resistance test: The carbon-coated aluminum foil was cut into 3×12.5 cm long strips. A cotton swab was dipped in N-methylpyrrolidone (NMP) and rubbed back and forth at a uniform speed on the carbon coating layer on the surface of the carbon-coated aluminum foil. The color change and peeling phenomenon of the carbon coating layer were observed visually.

[0129] (3) Sheet resistance test: The carbon-coated aluminum foil was cut into 10×10 cm square foils, and then the sheet resistance of the carbon-coated layer surface was tested using a double-probe sheet resistance tester. The thickness of the carbon-coated layer needed to be tested before the test.

[0130] The test results are summarized in Table 2.

[0131] Table 2

[0132] Solvent resistance Sheet resistance of carbon-coated foil (mΩ / square) Example 1 200 coatings without change 118.1 / 109.4 / 100.0 / 93.1 / 99.6 Example 2 200 coatings without change 78.1 / 62.6 / 77.4 / 78.3 / 80.6 Example 3 200 coatings without change 79.2 / 80.6 / 82.5 / 78.1 / 80.1 Example 4 200 coatings without change 113.5 / 99.1 / 107.6 / 126.2 / 101.5 Example 5 200 coatings without change 85.6 / 89.1 / 92.0 / 86.1 / 98.3 Example 6 200 times coating color faded 131.4 / 128.1 / 115.4 / 120.1 / 142.4 Example 7 200 times coating color faded 151.2 / 148.8 / 164.3 / 163.0 / 156.9 Example 8 200 times coating color faded 183.1 / 176.4 / 181.0 / 199.1 / 178.6 Example 9 200 times coating color faded 180.2 / 179.8 / 167.5 / 189.7 / 174.4 Example 10 200 times coating color faded 169.8 / 169.3 / 177.6 / 190.1 / 177.7 Comparative Example 1 200 times coating slightly peeled off 278.7 / 283.2 / 291.0 / 276.9 / 281.4 Comparative Example 2 200 times coating slightly peeled off 252.3 / 267.0 / 254.7 / 243.3 / 269.9 Comparative Example 3 200 times coating color faded 253.0 / 249.8 / 260.1 / 246.4 / 238.9

[0133] From the analysis of Comparative Example 1, Comparative Example 2 and Example 2, it can be seen that the carbon black prepared by adding alkali metal ion compounds, nitrogen-containing organic matter and / or phosphorus-containing organic matter in step (2) of the present application has better physical and chemical adsorption capacity and conductivity, and the composite current collector further formed has better solvent resistance and conductivity, which is conducive to the formation of a battery with excellent comprehensive performance.

[0134] From the analysis of Comparative Example 3 and Example 2, it can be seen that the carbon black obtained by the preparation method described in the present application has better physical and chemical adsorption capacity and conductivity than the products of the prior art, and the composite current collector further formed has better solvent resistance and conductivity, which is conducive to the formation of a battery with excellent comprehensive performance.

[0135] From the analysis of Example 8 and Example 2, it can be seen that the addition of a dispersant during the preparation of the present application can obtain carbon black with better physical and chemical adsorption capacity and conductivity, and the composite current collector further formed has better solvent resistance and conductivity, which is conducive to the formation of a battery with excellent comprehensive performance.

[0136] From the analysis of Examples 9-10 and Example 2, it can be seen that in the preparation of the present application, the total mass of the solid matter after drying is 100%, the mass of the alkali metal ion compound is greater than 0%, and is less than or equal to 300%, and the mass of the nitrogen-containing organic matter and / or phosphorus-containing organic matter is greater than 0%, and is less than or equal to 300%. The physical and chemical adsorption capacity and conductivity of the obtained carbon black are better, and the composite current collector further formed has better solvent resistance and conductivity, which is conducive to the formation of a battery with excellent comprehensive performance.

[0137] 3. Performance test of positive electrode

[0138] (1) Preparation of positive electrode sheet: First, 9.53 parts by weight of polyvinylidene fluoride (PVDF) was dispersed in 149.2 parts by weight of NMP at 300 rpm for 2 h to dissolve, then 3.18 parts by weight of commercial conductive carbon black Super P Li was added to the above solution and dispersed at 2500 rpm for 4 h, then the speed was reduced to 600 rpm, 304.8 parts by weight of lithium iron phosphate was added in three times, and then 33.3 parts by weight of NMP was added, and then the speed was further dispersed at 3000 rpm for 2 h, and finally the speed was reduced to 500 rpm to defoam the slurry for 1 h to obtain positive electrode slurry. The entire positive electrode slurry preparation process needs to be carried out under a protective atmosphere of nitrogen;

[0139] The positive electrode slurry was taken out, and then a 120 μm scraper was used on an automatic coating machine to coat the positive electrode slurry on the carbon-coated surface of the single-sided carbon-coated aluminum foil (the carbon-coated aluminum foil is the carbon-coated aluminum foil prepared in the above performance test) at a coating rate of 50 mm / s. The positive electrode was then transferred to a 100°C oven and dried for 30 minutes to obtain a positive electrode sheet. The positive electrode sheet was rolled using an automatic roller press for testing.

[0140] In order to compare the performance, a new comparative example 4 is added, which uses dual photovoltaic cell aluminum foil as the positive electrode current collector for comparison.

[0141] (2) Peel strength test: The peel strength test was conducted using a 180° peeling method; specifically, the positive electrode sheet was cut into 2.5×12.5 cm long strips, and then the coated surface of the positive electrode sheet was pasted on a stainless steel plate with double-sided tape and compacted. The free end of the positive electrode sheet was adhered to another stainless steel plate with transparent tape and then horizontally bent 180°. The two stainless steel plates were then pasted on the upper and lower test clamps of a tensile testing machine and continuously peeled at a tensile speed of 100 mm / min until the positive electrode sheet and the coating were completely separated, thereby obtaining the peel strength test result.

[0142] (3) Sheet resistance test: The positive electrode sheet is cut into 10×10 cm square sheets, and then the sheet resistance of the positive electrode coating surface is tested using a dual-probe sheet resistance tester. The thickness of the positive electrode material layer needs to be tested before the test.

[0143] The test results are summarized in Table 3.

[0144] Table 3

[0145]

[0146]

[0147] From the analysis of Comparative Example 1, Comparative Example 2 and Example 2, it can be seen that the carbon black prepared by adding alkali metal ion compounds, nitrogen-containing organic matter and / or phosphorus-containing organic matter in step (2) of the present application has better physical and chemical adsorption capacity and conductivity, and the composite current collector further formed has a greater peel strength with the active layer, and the internal resistance of the electrode is lower, which is conducive to the formation of a battery with excellent comprehensive performance.

[0148] From the analysis of Comparative Example 3 and Example 2, it can be seen that the carbon black obtained by the preparation method described in the present application has better physical and chemical adsorption capacity and conductivity than the products of the prior art. The composite current collector further formed has a greater peeling strength with the active layer, and the internal resistance of the electrode is lower, which is conducive to the formation of a battery with excellent comprehensive performance.

[0149] From the analysis of Example 8 and Example 2, it can be seen that the present application adds a dispersant during the preparation, and the physical and chemical adsorption capacity and conductivity of the obtained carbon black are better. The peeling strength between the composite current collector and the active layer is further greater, and the internal resistance of the electrode is lower, which is conducive to the formation of a battery with excellent comprehensive performance.

[0150] From the analysis of Examples 9-10 and Example 2, it can be seen that in the preparation of the present application, the total mass of the solid matter after drying is 100%, the mass of the alkali metal ion compound is greater than 0%, and is less than or equal to 300%, and the mass of the nitrogen-containing organic matter and / or phosphorus-containing organic matter is greater than 0%, and is less than or equal to 300%. The physical and chemical adsorption capacity and conductivity of the obtained carbon black are better, and the peeling strength between the composite current collector and the active layer formed is greater, and the internal resistance of the pole piece is lower, which is conducive to the formation of a battery with excellent comprehensive performance.

[0151] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A method for preparing carbon black, characterized in that: The preparation method comprises the following steps: (1) mixing a cellulosic biomass material and an acid solution, and then performing solid-liquid separation to obtain a solid; (2) The solid obtained in step (1), the alkali metal ion-containing compound, and the nitrogen-containing organic matter and / or the phosphorus-containing organic matter are mixed, calcined and impurity-removed to obtain carbon black.

2. The preparation method according to claim 1, characterized in that: In step (1), the cellulosic biomass material includes any one of bamboo straws, hemp straws or corn straws, or a combination of at least two of them.

3. The preparation method according to claim 1, characterized in that: In step (1), the acid used in the acid solution includes any one of nitric acid, hydrochloric acid or sulfuric acid, or a combination of at least two thereof; Preferably, in step (1), the mixed raw materials further include a dispersant; Preferably, the dispersant comprises any one of polyvinyl pyrrolidone, poloxamer or polyethylene glycol, or a combination of at least two thereof; Preferably, the mixing temperature is 30-70°C; and / or; The mixing time is 2-5h.

4. The preparation method according to claim 1, characterized in that: In step (2), the alkali metal ion-containing compound includes any one of potassium citrate, potassium oxalate, potassium acetate, potassium glycerol, potassium sulfate, potassium nitrate, potassium hydroxide or potassium chloride, or a combination of at least two thereof; Preferably, in step (2), based on the total mass of the solid matter after drying being 100%, the mass of the alkali metal ion-containing compound is greater than 0% and less than or equal to 300%.

5. The preparation method according to claim 1, characterized in that: In step (2), the nitrogen-containing organic matter includes any one of urea, melamine or biuret, or a combination of at least two thereof; Preferably, the phosphorus-containing organic compound includes any one of triphenylphosphine, triphenylphosphine oxide or tri(o-tolyl)phosphine, or a combination of at least two thereof; Preferably, in step (2), based on the total mass of the dried solid matter being 100%, the mass of the nitrogen-containing organic matter and / or the phosphorus-containing organic matter is greater than 0% and less than or equal to 300%; Preferably, in step (2), the calcination temperature is 700-900° C.; and / or; The calcination time is 1-3h; Preferably, in step (2), the impurity removal method includes mixing the calcined material with an aliphatic organic acid to remove alkali metal ions; Preferably, the aliphatic organic acid comprises oxalic acid.

6. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: (1) mixing a cellulosic biomass material, an acid solution and a dispersant, and then performing solid-liquid separation to obtain a solid; (2) The solid obtained in step (1), the alkali metal ion-containing compound, and the nitrogen-containing organic matter and / or the phosphorus-containing organic matter are mixed, and calcined at 700-900° C. for 1-3 h, and the calcined material is mixed with an aliphatic organic acid to remove the alkali metal ions to obtain carbon black.

7. A carbon black, characterized in that The carbon black is obtained by the preparation method according to any one of claims 1 to 6; Preferably, the specific surface area of ​​the carbon black is 80-130 m 2 / g; Preferably, the oil absorption value of the carbon black is 200-285 mL / 100 g.

8. A composite current collector, characterized in that: The composite current collector comprises a current collector and a carbon layer disposed on at least one surface of the current collector; The carbon layer comprises carbon black obtained by the preparation method according to any one of claims 1 to 6, or the carbon black according to claim 7.

9. An electrode plate, characterized in that: The electrode plate comprises the carbon black obtained by the preparation method according to any one of claims 1 to 6, or the carbon black according to claim 7, or the composite current collector according to claim 8.

10. A battery, characterized in that: The battery comprises the carbon black obtained by the preparation method according to any one of claims 1 to 6, or the carbon black according to claim 7, or the composite current collector according to claim 8, or the electrode plate according to claim 9.